1997
DOI: 10.1111/j.1151-2916.1997.tb03046.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ordering‐Induced Domain Boundaries on Low‐Loss Ba(Zn1/3Ta2/3)O3‐BaZrO3 Perovskite Microwave Dielectrics

Abstract: Small substitutions of BaZrO, into Ba[(Zn,Ni),Ta,]O, are utilized in the commercial preparation of low-loss perovskite microwave dielectrics. The structures of a series of these phases with substitution levels ranging from 1% to 5% BaZrO, were examined using high-resolution TEM.For I2.15% BaZrO, the solid solutions retain the ordered "1:2" structure of the Ba[(Zn,Ni),,Ta,]O, end-member but are comprised of small ordered domains whose size decreases as the Zr content is raised. The decrease in the size of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
204
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(220 citation statements)
references
References 28 publications
14
204
1
1
Order By: Relevance
“…[15]. Davies et al [15] have found that the formation of 1:2 ordered structure in these materials starts in small-size domains distributed in the disordered matrix [15]. They have shown the important role of Zr 4+ in the stabilization of domain walls that facilitates ordering processes in a material, and hence improves its Q-factor magnitude.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15]. Davies et al [15] have found that the formation of 1:2 ordered structure in these materials starts in small-size domains distributed in the disordered matrix [15]. They have shown the important role of Zr 4+ in the stabilization of domain walls that facilitates ordering processes in a material, and hence improves its Q-factor magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, by varying both -the ratio between the A-site ions (change in x) and the concentration of substituting ion in the BLTss, we can obtain the materials with high permittivity and quality-factor, and near-zero controllable temperature coefficient τ f (Table I). [15]. Davies et al [15] have found that the formation of 1:2 ordered structure in these materials starts in small-size domains distributed in the disordered matrix [15].…”
Section: Resultsmentioning
confidence: 99%
“…Using the lattice parameters obtained from XRD [δ = ðq x sub − q x film Þ ̸ q x film = + 0.0435], the estimated dislocation spacing is 8.7 nm, suggesting that the dislocations fully relax the strain in the film. Although superspots originating from the (111) diffraction are often observed in AB 0.5 B' 0.5 O 3 compositions that crystallize in B-site-ordered double perovskite structures [26], they are not observed in the SrTi 0.5 Nb 0.5 O 3 film (Fig. 10.4b).…”
Section: Pulsed Laser Depositionmentioning
confidence: 99%
“…When developing high-Q materials, properties such as crystal-structure dynamics, tolerance factors, electronic and atomic structure, etc have to be considered. These fundamental properties translate into several structural criteria that must be met in order to produce the high-Q material: the structure must be packed as close as possible [1,2]; different ions residing at the particular crystallographic site should differ in size as little as possible [3]; the cation ordering should be induced to reduce the anharmonicity of the crystal-lattice dynamics and eliminate the effects of the disordered charge distribution and further constrain the structure [4,5]; the reduction (or oxidation) of the ceramics must be avoided to suppress the conductivity [6]; the concentration of structural defects must be minimized and not associated with the strain fields [4]; the ceramics must be free of deleterious secondary phases [7]; and the grain boundaries must be clean of precipitates and liquid phase [8].…”
Section: New Dielectrics With High Q-valuesmentioning
confidence: 99%